Pharmacokinetics of Intravenous Voriconazole in Obese Patients: Implications of CYP2C19 Homozygous Poor Metabolizer Genotype. Issue 3 (11th February 2013) - Moriyama, Brad; Jarosinski, Paul F.; Figg, William D.; Henning, Stacey A.; Danner, Robert L.; Penzak, Scott R.; Wayne, Alan S.; Walsh, Thomas J.
<x xml:space="preserve">Abstract</x> There is a paucity of pharmacokinetic studies describing weight‐based dosing of intravenous voriconazole in obese patients. In this case report, we describe the pharmacokinetics of intravenous voriconazole in an obese CYP2C19 homozygous poor metabolizer and review previously reported data regarding the use of intravenous voriconazole in obese patients. A 17‐year‐old obese Hispanic male patient (body mass index 35 kg/m2) received intravenous voriconazole for the treatment of suspected aspergillosis. After 2.5 days of voriconazole 4 mg/kg intravenously every 12 hours based on adjusted body weight, the voriconazole area under the serum concentration–time curve over the course of a single (12‐hr) dosing interval and trough concentration were 86, 100 ng · hr/ml and 6.2 µg/ml, respectively. Six days later, the voriconazole dosage was decreased. A trough concentration measured just before the dosage reduction (after 8.5 days of voriconazole 4 mg/kg intravenously every 12 hours based on adjusted body weight) remained elevated at 5.8 µg/ml. Genotyping revealed a CYP2C19 homozygous poor metabolizer (CYP2C19*2/*2). Voriconazole was subsequently discontinued due to QTc prolongation. These data and those from two recent publications suggest that voriconazole does not distribute extensively into human adipose tissue and that obese patients should be dosed on an adjusted body weight basis. If an obese patient dosed on total body weight is also a CYP2C19 poor metabolizer, serum voriconazole concentrations will be further elevated, potentially leading to drug‐induced toxicity.